Belanja Online dan Jebakan Budaya Hidup Digital pada Masyarakat Milenial - Hasan Sazali; Fakhrur Rozi (Universitas Medan Area, 2020)
There purpose of this research is to find out how online shopping and the traps of digital living culture in millennial age people. The method used in research in the field is qualitative research methods, with a phenomenological approach. In conducting the research, it was found that the use of online shopping applications and online money loan (credit) applications is getting higher, of course, will lead to social pathology. Directly or indirectly, it can trap the millennial community in a circle of consumerism. Without literacy, communication and information technology (digital literacy) can lead to social pathologies and can turn into a trap for users who are determined by a digital lifestyle. Popular culture is always changing and appears uniquely in various places and times. The conclusion drawn from this study is that popular culture forms currents and eddies, and represents a complex interdependent-mutual perspective and values that affect society and its institutions in various ways. It is very likely that people at millennial age will also be trapped by this popular online shopping culture.